The effects of the Kalamazoo Promise scholarship on college enrollment, persistence, and completion - Timothy J. Bartik; Brad J. Hershbein; Marta Lachowska (W.E. Upjohn Institute for Employment Research, 2015)
We estimate the effects on postsecondary education outcomes of the Kalamazoo Promise, a generous place-based college scholarship. We identify Promise effects using difference-indifferences, comparing eligible to ineligible graduates before and after the Promise's initiation. According to our estimates, the Promise significantly increases college enrollment, college credits attempted, and credential attainment. Stronger effects occur for minorities and women. Predicted lifetime earnings effects of the Promise's credential gains, compared to the Promise's scholarship costs, represent an internal rate of return of 11.3 percent. Based on our results, simple and generous scholarships can significantly increase educational attainment and provide net economic benefits.
Keywords: I21; I22; I24; 330; place-based scholarship; enrollment; college completion; natural experiment; difference-in-differences; education policy